Effects of caffeine on resistance exercise: a review of recent research - Grgic, J. (Sports Medicine, 2021)
In the last few years, a plethora of studies have explored the effects of caffeine on resistance exercise, demonstrating that this field of research is growing fast. This review evaluates and summarizes the most recent findings. Given that toxic doses of caffeine are needed to increase skeletal muscle contractility, the binding of caffeine to adenosine receptors is likely the primary mechanism for caffeine`s ergogenic effects on resistance exercise. There is convincing evidence that caffeine ingestion is ergogenic for (i) one-repetition maximum, isometric, and isokinetic strength; and (ii) muscular endurance, velocity, and power in different resistance exercises, loads, and set protocols. Furthermore, there is some evidence that caffeine supplementation also may enhance adaptations to resistance training, such as gains in strength and power. Caffeine ingestion is ergogenic for resistance exercise performance in females, and the magnitude of these effects seems to be similar to that observed in men. Habitual caffeine intake and polymorphisms within CYP1A2 and ADORA2A do not seem to modulate caffeine`s ergogenic effects on resistance exercise. Consuming lower doses of caffeine (e.g., 2-3 mg/kg) appears to be comparably ergogenic to consuming high doses of caffeine (e.g., 6 mg/kg). Minimal effective doses of caffeine seem to be around 1.5 mg/kg. Alternate caffeine sources such as caffeinated chewing gum, gel, and coffee are also ergogenic for resistance exercise performance. With caffeine capsules, the optimal timing of ingestion seems to be 30-60 min before exercise. Caffeinated chewing gums and gels may enhance resistance exercise performance even when consumed 10 min before exercise. It appears that caffeine improves performance in resistance exercise primarily due to its physiological effects. Nevertheless, a small portion of the ergogenic effect of caffeine seems to be placebo-driven.